Compressed Sensing Based Video Multicast - Schenkel, Markus B.; Luo, Chong; Wu, Feng; Frossard, Pascal (Proceedings of SPIE Visual Communications and Image Processing (VCIP'2010), 2010)
We propose a new scheme for wireless video multicast based on compressed sensing. It has the property of graceful degradation and, unlike systems adhering to traditional separate coding, it does not suﬀer from a cliﬀ eﬀect. Compressed sensing is applied to generate measurements of equal importance from a video such that a receiver with a better channel will naturally have more information at hands to reconstruct the content without penalizing others. We experimentally compare diﬀerent random matrices at the encoder side in terms of their performance for video transmission. We further investigate how properties of natural images can be exploited to improve the reconstruction performance by transmitting a small amount of side information. And we propose a way of exploiting inter-frame correlation by extending only the decoder. Finally we compare our results with a diﬀerent scheme targeting the same problem with simulations and ﬁnd competitive results for some channel conﬁgurations.